Pengaruh Mononatrium Glutamat pada Pertumbuhan, Tanah, dan Hasil Bayam Hijau (Amaranthus gangeticus) - Safikah Lakulassa; Elisa Azura Azman; Roslan Ismail; Nor Elliza Tajidin (Jurnal Ilmu Pertanian Indonesia, 2022)
This study aims to influence the use of monosodium glutamate (MSG) on soil chemical properties and the growth and yield of green spinach (Amaranthus gangeticus) on Silabukan soil. Spinach is grown in polybags with six types of MSG treatment: without MSG (control), with 3, 6, 9, 12, and 15 g, with three repetitions. This study used a Complete Randomized Design, and the differences between treatments were analyzed using the least significant difference and Duncan methods. Observations were made under the auspices of rain at the Faculty of Agriculture Lestari, Universiti Malaysia Sabah, for four weeks. The parameters recorded are the components of plant growth, namely the circumference of the trunk, the number of leaves, the height of the tree, as well as the yield components in the form of wet weights and dry weights. The parameters of soil properties selected are soil pH, electrical conductivity, salinity, cation exchange rate, available-phosphorus, carbon content, hydrogen content, and aluminum exchange, taken before and after planting. Based on the analysis, the use of MSG negatively affects the growth and yield of green spinach. On the other hand, the control treatment showed very high growth and yield. Therefore, using MSG is not recommended to increase the growth and yield of green spinach grown in Silabukan soil. However, MSG increases the soil's pH, electrical conductivity, and salinity. Keywords: Amaranthus gangeticus, agricultural soil, green spinach, soil fertility, soil pH